Clinical Severity and Eosinophillic Count in Asthmatic Patients - Al-Husseiny, Auday Abd Al-Razaq (Indonesian Journal on Health Science and Medicine, 2025)
Inflammatory effects are caused by eosinophils, which are activated by allergens. Persistent airflow restriction is caused by ongoing airway remodeling and eosinophilic airway inflammation Although recent studies have failed to confirm this as a measure of severe asthma among adult asthma patients, high blood eosinophil levels were linked to severe asthma. Therefore, this study's goal was to ascertain whether a high blood eosinophil count and the severity of asthma are related. In 2024, a cross-sectional poll was carried out from January to December. A pre-tested structured questionnaire was used to collect data on clinical, behavioral, and sociodemographic traits. Four milliliters of venous blood were extracted from asthmatic patients in order to perform a complete blood count and assess peripheral morphology. Fifty-five (55.0%) of the 100 patients that were included in the trial were female, and forty-five (45.0%) were male. They ranged in age from 13 to 70. The range of the absolute eosinophil count was 70/mm3 to 1400/mm3. According to the severity criteria for asthma, 15 patients (15.0%) had severe asthma, 56 patients (56.0%) had moderate asthma, and 29 patients (20.0%) had mild asthma. This study aimed to evaluate the relationship between the eosinophil count in the blood and the severity of the illness. However, the study discovered a link between these two variables, indicating a relationship between peripheral eosinophil count and asthma severity. Highlights: Among 100 asthma patients, 15% had severe asthma, 56% moderate, and 29% mild, with higher eosinophil counts linked to greater severity. Patients with eosinophil counts >1000/mm³ showed the strongest association with severe asthma (p = 0.001). Findings support blood eosinophil count as a useful indicator for predicting asthma severity and guiding management.